2023
DOI: 10.1152/ajpregu.00057.2023
|View full text |Cite
|
Sign up to set email alerts
|

Loss of hepatic PPARα in mice causes hypertension and cardiovascular disease

Abstract: The leading cause of death in patients with non-alcoholic fatty liver disease (NAFLD) is cardiovascular disease (CVD). However, the mechanisms are unknown. Mice deficient in hepatocyte PPARα ( PparaHepKO) exhibit hepatic steatosis on a regular diet, making them prone to manifesting NAFLD. We hypothesized that the PparaHepKO mice might be predisposed to poorer cardiovascular phenotypes due to increased liver fat content. We use PparaHepKO and littermate control mice fed a regular chow diet to avoid complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 103 publications
1
11
0
Order By: Relevance
“…These mice exhibit hepatic steatosis in the absence of obesity, insulin resistance, and alterations in plasma triglycerides and lipids. 13 We observed that the Ppara HepKO mice are also hypertensive, and exhibit left ventricular remodeling with altered cardiac function and vascular stiffness. 13 Thus, this mouse model provides an opportunity to examine the impact of MASLD on the cardiovascular system, including the heart, in the absence of confounding effects of obesity and obesity‐associated metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…These mice exhibit hepatic steatosis in the absence of obesity, insulin resistance, and alterations in plasma triglycerides and lipids. 13 We observed that the Ppara HepKO mice are also hypertensive, and exhibit left ventricular remodeling with altered cardiac function and vascular stiffness. 13 Thus, this mouse model provides an opportunity to examine the impact of MASLD on the cardiovascular system, including the heart, in the absence of confounding effects of obesity and obesity‐associated metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 76%
“… 13 We observed that the Ppara HepKO mice are also hypertensive, and exhibit left ventricular remodeling with altered cardiac function and vascular stiffness. 13 Thus, this mouse model provides an opportunity to examine the impact of MASLD on the cardiovascular system, including the heart, in the absence of confounding effects of obesity and obesity‐associated metabolic abnormalities. The present study was designed to determine the mechanisms responsible for the alterations in cardiac function in Ppara HepKO mice.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations